Probabilistic Reasoning about Actions in Nonmonotonic Causal Theories - Eiter, T; Lukasiewicz, T (Morgan Kaufmann, 2003)
We present the language PC+ for probabilistic reasoning about actions, which is a generalization of the action language C+ that allows to deal with probabilistic as well as nondeterministic effects of actions. We define a formal semantics of PC+ in terms of probabilistic transitions between sets of states. Using a concept of a history and its belief state, we then show how several important problems in reasoning about actions can be concisely formulated in our formalism.